Inhibitory Action of Pisatin, a Phytoalexi'm of Pisum Sativum, for Spore Germination of Plant Fungi. - Siti Muslimah Widyastuti; Fukuji Nonaka; Nobumichi Sako; Kinji Tanaka (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1989)
-